2019
DOI: 10.3390/genes10080585
|View full text |Cite
|
Sign up to set email alerts
|

Untangling the Genetics of Human Longevity—A Challenging Quest

Abstract: Human average life expectancy in developed countries has increased dramatically in the last century, a phenomenon which is potentially accompanied by a significant rise in multi-morbidity and frailty among older individuals.[...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…Twin studies suggested a heritability of life span close to 25% (Dato et al, 2019). To date, only a few genetic variants in the following genes have been linked to longevity in different populations: APOE (APOE/TOMM40), FOXO3А, CDKN2B-AS1, and locus 5q33.3 (Kunizheva et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twin studies suggested a heritability of life span close to 25% (Dato et al, 2019). To date, only a few genetic variants in the following genes have been linked to longevity in different populations: APOE (APOE/TOMM40), FOXO3А, CDKN2B-AS1, and locus 5q33.3 (Kunizheva et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…To date, only a few genetic variants in the following genes have been linked to longevity in different populations: APOE (APOE/TOMM40), FOXO3А, CDKN2B-AS1, and locus 5q33.3 (Kunizheva et al, 2022). These variants explain only a small part of the estimated heritability of human longevity (Dato et al, 2019). The mechanisms regulating the longevity on population levels remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…The demographic and epidemiological transition has contributed to a growing increase in the proportion of older people in the world, whose numbers are estimated to reach 1.4 billion by 2030 and 2.1 billion by 2050, and could rise to 3.2 billion in 2100 [ 1 ]. Longevity is a multifactorial and complex characteristic, with the contribution of genetic and environmental factors [ 2 , 3 ]. Differences in socioeconomic, demographic, cultural and lifestyle conditions can influence the life expectancy of the population [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%